PENINGKATAN SARANA PRASARANA K3 DI BANK SAMPAH BECIK RESIK SUMBERMULYO SEBAGAI UPAYA MENINGKATKAN KESELAMATAN KERJA - Sulistyaningsih, Eka; Hariyanto, Satriawan Dini; Emaputra, Andrean (Jurnal Abdi Insani, 2024)
Waste banks are the activities that teach the community to sort waste and raise public awareness about wise waste management, which in turn will reduce the amount of waste transported to landfills. (Tempat Pembuangan Akhir). One of the actively operating waste banks in Bantul is the Bank Sampah Becik Resik. The Bank Sampah Becik Resik not only processes waste but is also often used as an educational place for waste management for those who want to learn how to process waste. However, in daily operations, the Becik Resik waste bank does not yet have Occupational Health and Safety facilities and infrastructure. (K3). Considering the situation and the issues, to address the limitations of K3 facilities and infrastructure, community service was conducted to improve K3 facilities and infrastructure as well as training on K3 and the use of fire extinguishers (APAR). The enhancement of K3 facilities and infrastructure is expected to raise awareness about the importance of K3 management. The facilities and infrastructure also aim to strengthen the role of the waste bank as an agent of change in environmental preservation efforts. The method of community service began with surveys and interviews with the managers regarding the K3 facilities and infrastructure needed, followed by floor painting according to K3 regulations, the provision of Fire Extinguishers (APAR), and K3 posters. The results of the Community Service (PkM) activities show that the Becik Resik Waste Bank room is now equipped with Occupational Safety and Health (K3) signs installed on the floor, Fire Extinguishers (APAR), and posters educating about K3 and waste management. In addition to the improvement of facilities, the team also provided K3 training and the use of fire extinguishers (APAR) to the partners. Through this training, the partners gained a deeper understanding of the importance of workplace safety and the emergency steps that need to be taken in case of a fire. With the enhancement of K3 facilities and the training provided, the partners' awareness in waste management and maintaining safety in the workplace has increased.